Relative criticalness of common laboratory tests for critical value reporting. Issue 4 (28th December 2018) - Yang, Zhutian; Tan, Eng Hooi; Li, Yingda; Lim, Brian; Metz, Michael Patrick; Loh, Tze Ping
Abstract : We determined the relative strengths of association between 23 most commonly ordered laboratory tests and the adverse outcome as indicators of relative criticalness. The lowest and highest results for 23 most commonly ordered laboratory tests, 24 hours prior to death during critical care unit (CCU) stay or discharge from CCU were extracted from a publicly available CCU database (Medical Information Mart for Intensive Care-III). Following this, the Random Forest model was applied to assess the association between the laboratory results and the outcomes (death or discharge). The mean decrease in Gini coefficient for each laboratory test was then ranked as an indication of their relative importance to the outcome of a patient. In descending order, the 10 laboratory tests with the strongest association with death were: bicarbonate, phosphate, anion gap, white cell count (total), partial thromboplastin time, platelet, total calcium, chloride, glucose and INR; moreover, the strength of association was different for critically high versus low results.